Multicolor combinatorial probe coding for real-time PCR. - Qiuying Huang; Linlin Zheng; Yumei Zhu; Jiafeng Zhang; Huixin Wen; Jianwei Huang; Jianjun Niu; Xilin Zhao; Qingge Li (PLoS ONE, 2011)
The target volume of multiplex real-time PCR assays is limited by the number of fluorescent dyes available and the number of fluorescence acquisition channels present in the PCR instrument. We hereby explored a probe labeling strategy that significantly increased the target volume of real-time PCR detection in one reaction. The labeling paradigm, termed "Multicolor Combinatorial Probe Coding" (MCPC), uses a limited number (n) of differently colored fluorophores in various combinations to label each probe, enabling one of 2(n)-1 genetic targets to be detected in one reaction. The proof-of-principle of MCPC was validated by identification of one of each possible 15 human papillomavirus types, which is the maximum target number theoretically detectable by MCPC with a 4-color channel instrument, in one reaction. MCPC was then improved from a one-primer-pair setting to a multiple-primer-pair format through Homo-Tag Assisted Non-Dimer (HAND) system to allow multiple primer pairs to be included in one reaction. This improvement was demonstrated via identification of one of the possible 10 foodborne pathogen candidates with 10 pairs of primers included in one reaction, which had limit of detection equivalent to the uniplex PCR. MCPC was further explored in detecting combined genotypes of five β-globin gene mutations where multiple targets were co-amplified. MCPC strategy could expand the scope of real-time PCR assays in applications which are unachievable by current labeling strategy.